Honduras: Labor Precarity in the Salaried Class During the Model of Neoliberal Accumulation - Mario Enrique Pineda Talavera (Íconos, 2019)
This article analyzes how labor relations have become precarious for the salaried class since the neoliberal model of accumulation in Honduras has been in place. In this paper, labor precarity is considered the deterioration and restriction of central labor status for the reproduction of the work force and the betterment of life conditions of the salaried masses. In terms of methodology, a simple index was elaborated to capture the empirical labor precarity and, subsequently, an estimation wasobtained from a logical binary regression which shows the determinant factors of high labor precarity in the years 2006, 2010, and 2013.